MATHEMATICAL COMPARISON OF TWO WELL-KNOWN PATTERNS OF MATERIAL EQUATIONS FOR GYROTROPIC MEDIA - Galumian, A. G.; Arakelian, H. M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
Two wave equations for isotropic, heterogeneous naturally gyrotropic media, based on two well-known formula of material equations are derived. It is shown that under certain conditions there exist substantial distinctions between solutions of wave equations corresponding to the two aforesaid equations.